A new species of Herminium (Orchidoideae, Orchidaceae) from Nepal - Raskoti, Bhakta Bahadur (Phytotaxa, 2013)
Herminium Linnaeus (1758: 251) is a genus of about 30 species, which are collectively distributed mainly inthe Himalayas with few species extending into Europe, central Asia, and southeastern Asia (Pridgeon et al. 2001, Pearce & Cribb 2002, Chen et al. 2009). The genus is characterized by its terrestrial or rarely epiphytic habitat, a concave lip base that is not auriculate and does not have any glands, a lip 2–3 (–5) that is lobed, not spurred and a bilobed stigma with an obscure rostellum. Nepal has nine species of Herminium, which are distributed in the subtropical to alpine regions (Hara et al. 1978, Banerji 1984, Banerji & Pradhan 1984, Press et al. 2000, Department of Plant Resources 2001, Rajbhandari & Dahal 2004; Rajbhandari & Baral 2010). During field work in 2012 in Chandragiri, central Nepal, another species of Herminium was collected, the characteristics of which do not match with any previously described species of the genus. It is illustrated and described here as new.